Reimagining Policy Spaces: Toward Accessible and Inclusive Public Engagement - Dobrowolsky, Alexandra; Findlay, Tammy; Acker-Verney, Julianne M.; Cattapan, Alana; O’Keefe, Jennifer; Mandrona, April; Carroll, Jewelle (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2023)
This study interrogates the potentialities of policy spaces with the aim of bringing marginalized groups more concertedly into the centre of public policy engagement. By taking a feminist intersectional approach to examining the limits of classical public policy and conventional modes of public engagement, we propose a more fluid and generative understanding of policy space that encompasses both physical and social aspects and their interrelations. We then apply this understanding to our experimentation with two public engagement exercises held in Nova Scotia, a workshop and panel for disabled and Deaf women, and a podcast for rural women, that were part of a larger project aimed at acquiring in-depth, nuanced policy feedback from several, historically marginalized groups. Through our experience with these exercises—their successes and failures—we propose an approach to theorizing policy spaces informed by the contributions and interests of the groups in question, and with an awareness of intersectional power dynamics, positionality and place.